KETERAMPILAN DASAR BERMAIN FUTSAL DAN KONDISI FISIK SISWA EKSTRAKURIKULER FUTSAL SMA NEGERI 6 PONTIANAK - Riski Kurniawan; Ahmad Atiq; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2021)
AbstractThe problem in this study is how the basic skills of playing futsal and the physicalcondition of extracurricular students at SMA Negeri 6 Pontianak are. the researchmethod used is the test and measurement method with tests of basic futsal skills andfutsal physical conditions consisting of 20 extracurricular participants. ”: 7 players orequal to (35%), “medium” category: 6 players or equal to (30%), “less” category: 5players or equal to (25%), and “very less” category: 1 player or equal to (5%). Fromthe overall data, the basic skills of playing futsal at SMA Negeri 6 Pontianak are inthe